Damage diagnosis in an isotropic structure using an artificial immune system algorithm - Oliveira, Daniela C. [UNESP]; Chavarette, Fábio R. [UNESP]; Lopes, Mara L. M. [UNESP] (Springer Nature, 2019)
This work proposes a recent methodology for developing structural health monitoring based on intelligent computing techniques, with the purpose of detecting structural damages in aircrafts using artificial immune systems with negative selection. To assess this methodology, an experimental setup was built with piezoelectric transducers attached to an aluminum plate (which represents a wing of an airplane), which work both as actuators and sensors, where signals were acquired in normal and damage situations. The results show robustness and accuracy for the new methodology proposed.
Keywords: Artificial immune systems; Negative selection algorithm; Structural health monitoring